The Exchange Rate of RMB Affects Economic Growth: an Open Ramsey Model based on the Regulation of External Debt Stock - Wei Li , Chengke Zhu, Zhentian Su (Forest Chemicals Review, 1970)
The paper introduces real exchange rate into Ramsey Model, and also gives some numerical simulation about the effect of real exchange rate on economic growth. The paper constructs net foreign debt stock control open Ramsey model based on not fully open economic conditions. In the net foreign debt stock control open Ramsey model we found that:first, when, that is, when foreign debt interest rate is higher than consumption discount factor, the currency’s appreciation will make this country has less per capita effective capital on the balanced growth path, this is not conducive to a country’s economic growth in the long term. Second, when, that is, the foreign debt interest lower than consumption time discount factor, the currency’s appreciation will make this country has more per capita effective capital on the balanced growth path.